Development Of Assessment Instrument Based on Higher Order Thinking (Hot) Using Quizizz Application on The Subject of Reaction Rate for XI Grade High School Students - Rery, Radjawali Usman; Sangputri, Anisa Wulan; Albeta, Sri Wilda (Universitas Negeri Malang, 2023)
This study aims to produce an assessment instrument based on HOT using Quizizz application about a valid reaction rate by the validator, as well as to determine the validity, reliability, level of difficulty, discriminatory power, and user response. This study uses research and development (R&D) design with the Plomp model. The subjects in this study were 2 chemistry teachers and 20 class XII students at SMAN 8 Pekanbaru and SMAN 2 Pekanbaru. Data collection techniques were carried out by interviews, literature studies and field studies. For data analysis techniques used validation by experts, as well as user trials. The validation results for the material validator obtained an average based on material aspects of 99.33 percent, construction aspects of 94.61 percent and language aspects of 95.16 percent. According to the media validator based on the substance aspect of the content is 97.77 percent, learning design is 91.25 percent, display (visual communication) is 96.67 percent and software utilization is 100 percent. The results of the purification of the item analysis data obtained that 15-item multiple choice HOT questions the valid criteria, had very high reliability criteria, 10 items were obtained in the